ইলা মিত্র : নাচোলের তেভাগা আন্দোলনের নেত্রী - বেগম, মালেকা. (ঢাকা : প্রথমা প্রকাশন, 2023)
On the life and works of Ila Mitra, born in 1925, a Bengali woman political activist and communist of East Pakistan, now Bangladesh; includes some letters, interviews and articles by and about her.
প্রথম প্রকাশ ১৯৮৯
"Nacolera tebhaga andolanera netri"--Cover.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তভূক্ত
RS (GenEd)
Hye Trade International
Keywords: Mitra, Ila, -- 1925-2002.; Women political activists -- Bangladesh -- Biography; Women communists -- Bangladesh -- Biography; Femmes activists -- Bangladesh -- Biographies; Biography